CARBON ISOTOPIC COMPOSITION AND ORIGIN OF SIC FROM KIMBERLITES OF YAKUTIA, RUSSIA - Mathez E.A.; Fogel R.A.; Hutcheon I.D.; Marshintsev V.K. (My University, 1995)
The stability of moissanite (SiC) has been computed for upper mantle conditions using the internally optimized thermodynamic dataset for the Mg-Si-O compounds of Fei et al. (1990). The computations consider the effects of pressure and temperature on the elastic properties of phases involved in the reactions. The maximum stability of moissanite throughout the upper mantle is typically five to six orders of magnitude lower in oxygen fugacity (fO2) than the Fe metal-wüstite oxygen buffer at equivalent temperature and pressure, in agreement with previous calculations. Under conditions of SiC stability, silicates will be Fe-free, Fe metal will contain substantial amounts of Si but little C in solution, and Mg-rich sulfides will be stable.